PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA PERAWAT PADA RSUD TARUTUNG KABUPATEN TAPANULI UTARA - Retnowaty Hutagalung; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study uses 3 variables, namely job leadership, supervision and nurse work discipline. The job performance variable has 3 dimensions, namely able to work together, experts in a field and have spirit to move forward. In the supervision variable has 4 dimensions, namely setting standard, measuring performance, comparing performance with standartd and determining results with standard. On variables work discipline has 4 dimensions, namely attandance, responsibilitie, attitude and norm. The sample used are PNS nurses at RSUD Tarutung North tapanuli Regency with 60 respondents. Data obtained from questionnaires and then processed then tested using statistical analysis such as validity test, reliability test, simple linear regression, multiple linear regression, determination test (R2), significant individual test (t test), and simultaneous significant test (f test) with using the SPSS program. The results of the study indicate the influence of leadership and supervision on nurse work discipline. The better leadership and supervision then it will increase and better nurse work discipline. The results of the calculation of the determination coefficient (R2) obtained the value of R Square of 0.629. The meaning is that the contribution of leadership variables and supervision on work discipline variable is 62.9%.  Keyword : Work Discipline, Leadership, Supervision